In your face : professional improprieties and the art of being conspicuous in sixteenth-century Italy - Biow, Douglas (Stanford University Press, 2010)
This study concentrates on the Renaissance concern with 'self-fashioning' by examining how a group of Renaissance artists and writers encoded their own improprieties in their works of art. In the elitist court society of sixteenth-century Italy, where moderation, limitation, and discretion were generally held to be essential virtues, these men consistently sought to stand out and to underplay their conspicuousness at once.